An investigation into factors influencing rural youth entrepreneurs' intentions to use ICT: a case of Malaysia - Zaremohzzabieh, Zeinab; Abu Samah, Bahaman; Muhammad, Mahazan; Omar, Siti Zobidah; Bolong, Jusang; Mohamed Shaffril, Hayrol Azril (Inderscience Publishers, 2016)
Attention has been paid in Malaysia to the potential for information communication technology (ICT) being a key driver of competitive advantage, and the opportunity to benefit rural youth entrepreneurs. Thus, the aim of this study is to develop additional constructs, or 'entrepreneurial knowledge' (EK), to the entrepreneurial potential model (and thus validating it in the context of ICT) in order to augment factors influencing rural youth entrepreneurs' intention to use ICT. In this research, the data from 400 rural youth entrepreneurs were examined using SEM to analyse hypothesised causes as suggested in our proposed model. Results showed that attitude and EK significantly influenced the Malaysian rural youth entrepreneurial intention (EI) to use ICT. This paper demonstrates that the new model is capable of evaluating the causal flow that leads to the intentional behaviour between the suggested external factors and also makes useful contributions to the literature on EI, which could assist policymakers in creating successful ICT intervention strategies to support Malay rural youth entrepreneurs.